Bio-efficacy of the Essential Oil of Oregano (Origanum vulgare Lamiaceae. Ssp. Hirtum) - Grondona, Ezequiel (2014)
The aim of this study was to investigate the bioactivity of the essential oil isolated from Origanum vulgare L. (EOv). We analyzed the in vivo anti-inflammatory properties in a mouse-airway inflammation model and the in vitro antimicrobial activity, genotoxicity over the anaphase-telophase with the Allium cepa strain and its cytotoxicity/viability in A549 culture cells. In vivo, EOv modified the levels of tumor necrosis factor -α and viable activated macrophages and was capable to mitigate the effects of degradation of conjugated dienes. In vitro, EOv reduced the viability of cultured A549 cells as well as the mitotic index and a number of chromosomal aberrations; however, it did not change the number of phases. We found that EOv presents antimicrobial activity against different Gram (−) and (+) strains, measured by discdiffusion test and confirmed with a more accurate method, the AutoCad software. We postulate that EOv presents antibacterial, antioxidant and chemopreventive properties and could be play an important role as bioprotector agent.